Virtual reality : concepts and technologies - Fuchs, Philippe; Moreau, Guillaume; Guitton, Pascal (Boca Raton, FL : CRC Press, 2011)
'A manual for both designers and users, comprehensively presenting the current state of experts' knowledge on virtual reality (VR) in computer science, mechanics, optics, acoustics, physiology, psychology, ergonomics, ethics, and related area. Designed as a reference design guide to help the reader develop a VR project, it presents the importance of the users needs and various aspects of the human computer interface (HCI). It further treats technical aspects of VR, hardware and software implementations, and details on the sensory and psycho-sensory interfaces. Providing various concepts and technologies, including mathematics and modelling techniques, it allows the reader to formalize, conceptualize and construct a virtual reality project from original thought to application. For engineers, computer scientists and computer game developers and as an educational tool in courses for senior senior graduate students'--
Includes bibliographical references and index.
Translated from the French.
Keywords: Virtual reality